Public perceptions of the seriousness of crime: Weighing the harm and the wrong - Adriaenssen, An (European journal of criminology, 2020)
The seriousness of crime or ‘crime seriousness' bears on at least four areas of criminal policy (sentencing, criminalization, crime control and prevention) but is poorly defined. After providing a novel conceptualization of crime seriousness, this article explores the logic - or normative philosophical principles - behind the public's assessment of crime seriousness and considers how the public's logic aligns with legal principles and policy requirements. A general population survey administered in 2014 in Belgium and eliciting 1278 valid responses indicates that the public's logic is more moralist than consequentialist and raises doubts about the validity of public perceptions of crime seriousness as an indicator of crime seriousness for policy-making.